Isolation and characterization of aquatic-borne Klebsiella pneumoniae from tropical estuaries in Malaysia - Barati, A.; Ghaderpour, A.; Chew, L.L.; Bong, C.W.; Thong, Kwai Lin; Chong, V.C.; Chai, L.C. (MDPI, 2016)
Klebsiella pneumoniae is an opportunistic pathogen that is responsible for causing nosocomial and community-acquired infections. Despite its common presence in soil and aquatic environments, the virulence potential of K. pneumoniae isolates of environmental origin is largely unknown. Hence, in this study, K. pneumoniae isolated from the estuarine waters and sediments of the Matang mangrove estuary were screened for potential virulence characteristics: antibiotic susceptibility, morphotype on Congo red agar, biofilm formation, presence of exopolysaccharide and capsule, possession of virulence genes (fimH, magA, ugE, wabG and rmpA) and their genomic fingerprints. A total of 55 strains of K. pneumoniae were isolated from both human-distributed sites (located along Sangga Besar River) and control sites (located along Selinsing River) where less human activity was observed, indicated that K. pneumoniae is ubiquitous in the environment. However, the detection of potentially virulent strains at the downstream of Kuala Sepetang village has suggested an anthropogenic contamination source. In conclusion, the findings from this study indicate that the Matang mangrove estuary could harbor potentially pathogenic K. pneumoniae with risk to public health. More studies are required to compare the environmental K. pneumoniae strains with the community-acquired K. pneumoniae strains.